Information processing and intuitive decision-making on the fireground: towards a model of expert intuition. Issue 1 (February 2016) - Okoli, Justin; Weller, Gordon; Watt, John
Abstract In addition to other cognitive tasks that need attending to, experienced fireground commanders are also faced with a crucial task of identifying various environmental and informational cues that could affect their performance on the fireground. Although these cues play a crucial role in activating the pattern recognition or intuitive decision-making process, the major challenge remains that they usually emerge from multiple sources, thereby increasing the cognitive load in working memory. Previous studies have shown that attending to multiple informational sources has serious implications for intuitive decision-making as it then becomes more difficult to select the most relevant cues amidst the rapidly evolving conditions. In order to determine how firefighters cope with this difficult task of processing information from multiple sources, 16 experienced fireground commanders were interviewed using a semi-structured critical decision method protocol. Following the insights derived from the knowledge elicitation process, this paper presents and describes an expert intuition model, which we termed the information filtering and intuitive decision-making model. The model attempts to conceptualize how experienced firefighters scan through multiple information sources from which they are then able to select the most relevant cues that eventually aid the development of workable action plans.